Pemberdayaan Pelaku UMKM Oleh-Oleh Solo Raya Melalui Pelatihan Digital Marketing - Febrianur I. F. S. Putra; Awanis L. Haziroh; Diana Aqmala; Farrikh Al Zami; Ifan Rizqa; Abu Salam; Erin Kristina (Lembaga Pengembangan Kinerja Dosen, 2024)
The Internet advancement in Indonesia has created significant opportunities for digital business, particularly in marketing. Digital marketing encompasses promoting products and services through online platforms, such as social media, which facilitate connections among individuals globally. Micro, Small, and Medium Enterprises (MSMEs) are anticipated to play a crucial role in bolstering economic growth, especially within the food and beverage sector, alleviating unemployment. Despite many MSMEs needing to leverage social media entirely, they are progressively adapting their promotional strategies and discount offerings in response to the challenges posed by the COVID-19 pandemic. This community service initiative employs digital marketing as a strategic approach to facilitate market penetration for MSMEs in the culinary field, thereby enhancing sales. It is anticipated that this initiative will address the difficulties encountered by culinary partners, particularly the lack of marketing innovation due to inadequate skills in managing social media marketing. Furthermore, the pursuit of business volume targets is complicated by escalating competition within the culinary sector. The proposed short-term solutions include promoting the use of social media for product marketing and encouraging product innovation.